A deadly combination of AIDS, TB and cardiac tumour. (22nd May 2013) - Sahasrabudhe, Tushar Ramesh
Abstract : Immunocompromised status in AIDS makes differential diagnosis of any symptom very difficult for a clinician. Sharp clinical judgement and plenty of investigations may be needed to reach the diagnosis, as in this case. We hereby present a case of AIDS and active tuberculosis (TB) under treatment. The patient developed acute onset multifocal neurological symptoms following an episode of fever and diarrhoea. The MRI scan revealed numerous large cerebral infarcts. On investigations to evaluate brain infarcts, we made a diagnosis of left atrial cardiac tumour. Association of cardiac tumours with AIDS has only been rarely reported. It is uncertain if these can be opportunistic tumours in AIDS. The patient successfully came out of this deadly combination of diseases, viz AIDS, TB and large brain infarcts due to atrial tumour; with almost complete recovery.